Penanaman Pendidikan Karakter Profil Pelajar Pancasila Melalui Kegiatan Ekstrakurikuler Pramuka - Siska Afresda; Moh. Toharudin; Diah Sunarsih (Departement of Mathematics Education, 2023)
This study aims to be able to describe how the inculcation of character education on Pancasila student profiles and supporting factors and inhibiting factors on Pancasila student profile character education through scout extracurricular activities. This research method is a qualitative research using a phenomenological approach. The research location was at Pamedaran 02 Public Elementary School. The informants in this study were class IV students and Scoutmasters. Based on the results of the study, it was concluded that the inculcation of Pancasila student profile character education through scout extracurricular activities at SD Negeri Pamedaran 02 includes: (1) Faithful, devoted to God Almighty and noble, (2) Global diversity, (3) Independent, (4) Working together, (5) Critical reasoning, and (6) Creative. Supporting factors in character education for Pancasila student profiles through scout extracurricular activities at Pamedaran 02 Public Elementary School, namely (1) There is self-awareness of students, (2) There is motivation, (3) There is collaboration with friends, and (4) There is support from parent. The inhibiting factors for character education of Pancasila student profiles through scout extracurricular activities at SD Negeri Pamedaran 02 are: (1) The absence of students even though they have been required by the scout coach to carry out scout activities, (2) The assumption of students that scout activities are hot and long , (3) There is no special room to carry out congregational prayers and the number of mukenas is limited, and (4) The weather factor.